Liberia : Request for Disbursement Under the Rapid Credit Facility and Debt Relief Under the Catastrophe Containment and Relief Trust. (IMF Staff Country Reports; Country Report, 2015)
This paper discusses Liberia's Request for Disbursement Under the Rapid Credit Facility (RCF) and Debt Relief Under the Catastrophe Containment and Relief (CCR) Trust. Economic activity has declined significantly, and fiscal and external financing needs are more pronounced than envisaged at the time of the Extended Credit Facility (ECF) augmentation. The authorities remain committed to the broad objectives of the ECF program. The IMF staff recommends approval of the authorities' requests for a disbursement under the RCF and debt relief under the CCR Trust given the extensive economic damage caused by the Ebola outbreak and based on the authorities' updated policy intentions and commitments.